An incremental approach to web service composition - Granell, Carlos; Poveda, José; Gould, Michael (Revista Colombiana de Computación, 2004)
Geographic web services will soon become subsumed in the e-commerce world, a world where the composition of simple or atomic services to build compound services is a key characteristic. Since currently no detailed model of composite geographic web services exists, and within the scope of work on a European Union-funded project, we define such basic composition as part of an effort to test for geographic web service interoperability. Rather than adopting current static methods, we build on the concept of incremental composition and provide a model for defining, composing and invoking compositions in a flexible manner. Keywords: Web service composition, incremental composition, semantic interoperability, interoperability testing.